Vault Haematoma after Vaginal Hysterectomy - Batish, A; Sathiyathasan, S; Jeyanthan, K (Nepal Journal of Obstetrics and Gynaecology, 2014)
Electronic searches of literature published between 1980 and 2014 were undertaken using MEDLINE, Embase, CINHAL, and the Cochrane Database of Systemic reviews. Search items included: haematoma, hysterectomy, morbidity, ultrasound. The incidence of vault hematomas varied from 25- 59 % in various studies. Small hematomas can be managed conservatively and large and infected hematomas need incision and drainage. However various studies found no correlation between the presence of a collection and indices of postoperative morbidity. Also routine scan was not indicated. The incidence of vault hematomas is due to inadequate haemostasis and refining the surgical technique significantly reduces the risk of vault hematomas. DOI: http://dx.doi.org/10.3126/njog.v9i2.11768